Formation of Tourism Terminology and Study of Translation Problems - Kuchqarova Gavharoy (Zien Journals, 2022)
The article deals with the field of terminology and its theoretical issues, in particular, terms related to tourism and their translation problems.
Keywords: term; terminological system; suffix; vocabulary